Defining Optimal Post-prison Care for Those With Psychosis: A Delphi Study - Simpson, Paul L.; Settumba, Stella; Adily, Armita; Ton, Bianca; Butler, Tony (Frontiers in Psychiatry, 2021)
Background: Early treatment (considered as early contact with community mental health services) and treatment retention are associated with reduced reoffending among those with a previous diagnosis of psychosis, yet the attributes of care required to best achieve this is largely unexplored for people with psychosis leaving prison. This study sought consensus from a sample of experts and consumers regarding the attributes of an ‘optimal model of care’ for those with a prior episode of psychosis leaving prison in New South Wales, Australia. Methods: A Delphi method was used, which involved establishing a consensus from a panel of 25 experts and consumers. Following three meetings, 34 model of care attributes and 168 attribute levels were generated for two rounds of online scoring. All attributes and levels were included in the final model if they scored ‘very important’ or ‘extremely important’; or if the attribute was agreed on by 70% or more of participants. The participant retention rate across scoring rounds was 96% for Round 1 and 84% for Round 2, where consensus was reached. Two ‘member checking’ procedures were undertaken to enhance the integrity of findings: a model ‘stress test’ and an online consumer poll. Results: Thirty-two attributes and 72 attribute levels were included in the final model across four components: pre-release care planning and coordination; treatments in community; diversion from prison; and evaluation. Member checking endorsed a person-centered approach with carers and peer-support central to care. Conclusions: Participants agreed that an optimal model of care should involve a specialized team who works independent of community health service teams to directly deliver certain treatments and services while helping consumers to access external social an economic supports and services.